Non Helicobacter pylori - Duodenal Ulcer in a Liver Cirrhosis Patient - Bayu Sukresno; Haryono Achmad (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2002)
Peptic ulcer is an clearly marginated ulceration in mucosal membran that can penetrate until muscularis layer and resulted from imbalance between aggressive factor (gastric acid and pepsin) and defensive factor (gastric mucous, bicarbonate and prostaglandin, mucosal blood flow, and cell replacement). Factors that can act as aggressive factor include H. pylori, NSAID, and smoking. Duodenal ulcer is frequently associated with H. pylori, in which Helicobacter pylori is found in 95 - 100% of duodenal ulcer patients.. It was reported, a 39 years old female patient with cirrhosis hepatis who suffered from melena in which endoscopic examination revealed duodenal ulcer as a source of bleeding.There was no H. pylori, based on serologic examination (IgG antiHP) and culture. The ulcer is suspected caused by  NSAID based on history of using traditional medicine that may contain NSAID. Treatment with proton pump inhibitor and sucralfate can heal the ulcer after two week treatment.    Keywords: H. pylori, duodenal ulcer – liver cirrhosis